2004
DOI: 10.1097/01.jom.0000141662.18277.07
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Disease in Aggregate Quarry Workers Related to Risk Factors and Pi Phenotype

Abstract: Radiologic alterations are found in relation to tobacco. The FEV1 has a negative relation with the product dust-tobacco. No alterations related to Pi phenotype are found. A subgroup with the highest alpha1-antitrypsin levels had more radiologic alterations and worse function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…However, several studies 33 , 34 show elevated CRP levels, a non-specific biomarker, in patients exposed to silica and increasing according to silicosis severity, as was the case in our study. Our series shows elevated levels of alpha-1-AT, in a similar fashion to Montes II et al 35 . The rise in plasma LDH concentration can be also detected in a variety of other processes, such as systemic infections or inflammations, muscle injuries, hemolysis, thromboembolism or malignancies.…”
Section: Discussionsupporting
confidence: 90%
“…However, several studies 33 , 34 show elevated CRP levels, a non-specific biomarker, in patients exposed to silica and increasing according to silicosis severity, as was the case in our study. Our series shows elevated levels of alpha-1-AT, in a similar fashion to Montes II et al 35 . The rise in plasma LDH concentration can be also detected in a variety of other processes, such as systemic infections or inflammations, muscle injuries, hemolysis, thromboembolism or malignancies.…”
Section: Discussionsupporting
confidence: 90%
“…21 In arids quarry workers, we have also seen a negative relation between percent predicted FEV1 and mg/m 3 -year of respirable dust multiplied by pack-years. 32 These results are consistent with the findings of Hnizdo 45 in gold mine workers and with the results of the communitybased study carried out by Xu et al 46 The main drawback of our study is its cross-sectional design, which is susceptible to important biases, particularly the healthy worker effect. In this case there should be a relation between exposure and disease, the bias would favor the null hypothesis and would not invalidate the positive findings.…”
Section: Silicosissupporting
confidence: 94%
“…This is in disagreement with results of a previous study conducted in arid quarries, in which we have found a significant positive relation between round opacities and cumulative exposure to respirable dust. 32 This lack of parallelism is remarkable and may be because the afore-mentioned study was performed in limestone quarry workers. Limestone dust contains scant amounts of free silica and the lesions observed were minimal with frequent irregular opacities whereas in the granite study silica exposure was high and there were numerous lesions capable of hiding faint tobacco-induced lesions.…”
Section: Silicosismentioning
confidence: 94%
“…These results confirm previous findings from our group that revealed the occurrence of obstructive and restrictive changes in lungs of silicotic mice (Ferreira et al ., ). The airway hyper‐reactivity verified is in agreement with findings in humans (Forastiere et al ., ; Montes et al ., ). It was shown that exposure to high concentrations of crystalline silica promotes an intense inflammatory response accompanied by cell proliferation and excessive deposition of collagen and other extracellular matrix components, resulting in the development of fibrosis (Mossman and Churg, ).…”
Section: Discussionmentioning
confidence: 97%